Catalysis of photooxidation reactions through transformation between Cu2+ and Cu+ in TiO2–Cu–MOF composites. Issue 47 (23rd May 2018) - Chen, Chunjun; Wu, Tianbin; Yang, Dexin; Zhang, Pei; Liu, Huizhen; Yang, Youdi; Yang, Guanying; Han, Buxing
Abstract : Novel porous TiO2 @Cu3 (BTC)2 composites, which were synthesized using ionic liquids (ILs) as solvents, exhibited excellent activity for photooxidation of styrene to 4-aryl tetralones and promoting the Glaser coupling reaction with O2 under light irradiation. Abstract : Novel porous TiO2 @Cu3 (BTC)2 composites, which were synthesized using ionic liquids (ILs) as solvents, exhibited excellent activity for photooxidation of styrene to 4-aryl tetralones and promoting the Glaser coupling reaction with O2 under light irradiation. It was discovered that the transformation between Cu 2+ and Cu + was crucial for enhancing the photocatalytic performance.